2018
DOI: 10.2337/db18-0184
|View full text |Cite|
|
Sign up to set email alerts
|

SRY-Box Containing Gene 4 Promotes Liver Steatosis by Upregulation of SREBP-1c

Abstract: Obesity is usually associated with an increased risk of nonalcoholic fatty liver disease that is characterized by accumulation of excessive triglyceride (TG) in hepatocytes. However, the factors involved in the obesity-induced hepatosteatosis are poorly defined. Here, we report that SRY-box containing gene 4 (), a transcription factor that regulates cell proliferation and differentiation, plays an important role in hepatic TG metabolism. expression levels are markedly upregulated in livers of obese rodents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…Among the SREBP isoforms, SREBP-1c predominantly regulates the transcription of genes participating in FFA synthesis, whereas SREBP-1a and SREBP-2 are associated with cholesterol synthesis [23]. Recently, SOX4, another member of the SOX family, has been shown to promote liver steatosis by directly regulating the transcription of SREBP-1c [24]. In the present study, the expression of SREBP-1a and SREBP-1c could not be observed, limiting our possible conclusions.…”
Section: Discussioncontrasting
confidence: 71%
“…Among the SREBP isoforms, SREBP-1c predominantly regulates the transcription of genes participating in FFA synthesis, whereas SREBP-1a and SREBP-2 are associated with cholesterol synthesis [23]. Recently, SOX4, another member of the SOX family, has been shown to promote liver steatosis by directly regulating the transcription of SREBP-1c [24]. In the present study, the expression of SREBP-1a and SREBP-1c could not be observed, limiting our possible conclusions.…”
Section: Discussioncontrasting
confidence: 71%
“…Those mRNAs revealed a trend towards the inverse patterns in A1cf -/liver (Supplemental Figure 7D). SOX4 overexpression in liver was shown to stabilize b-CATENIN, increase cell proliferation, promoting steatosis and HCC progression (29)(30)(31)(32), while SPARCL1 overexpression was correlated with tumor angiogenesis in HCC (33,34). Since SMAD9 inhibits Bone Morphogenetic Protein (BMP) signaling (34) we asked if the decreased expression of Smad9 in A1cf +/Tg liver was accompanied by changes in Bmp7 mRNA.…”
Section: Transcriptome-wide Analysis Of A1cf +/Tg Liver and Isolated mentioning
confidence: 99%
“…Li et al showed that inhibiting SREBP-1c activity can exert an anti-hepatic steatosis effect in diet-induced obese mice [3]. The correlation between inhibition of the SREBP-1c/FAS pathway and decreased liver lipid synthesis has been well established [1618]. Therefore, the activation of the AMPK/ACC/CPT-1A pathway and inhibition of the SREBP-1c/FAS pathways may be potential targets for screening drugs to prevent hepatic lipid accumulation.…”
Section: Introductionmentioning
confidence: 99%